High sensitivity H2S gas sensors using lead halide perovskite nanoparticles - Ahmad I. Ayesh (10188469) (2022)
We report the development of a high sensitivity H2S gas sensor based on perovskite nanoparticles, which can be synthesized using relatively simple solution-growth methods. The gas sensor was fabricated from the metal halide perovskite formamidinium lead bromide (FAPbBr3), which exhibits a high sensitivity to H2S gas in the form of changes to the electrical conductivity. The response of the sensor to H2S gas showed a high sensitivity to gas concentrations in the range 0.5 – 100 ppm, with a fast response time of less than one minute under ambient room conditions. Other Information Published in: Results in Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rinp.2022.105333